ANALISIS QoS (QUALITY OF SERVICE) PADA JARINGAN INTERNET (STUDI KASUS : UPT LOKA UJI TEKNIK PENAMBANGAN JAMPANG KULON – LIPI) - Rika Wulandari (Maranatha University Press, 2016)
Abstract – Technical Implementation Unit for Mine’s Technology Assessment Jampang Kulon - LIPI, organizationally under and responsible to the Head of Geotechnology Research Center, Deputy of Earth Sciences, Indonesian Institute of Sciences. To support research and development activities, administration and cooperation is in need of Internet-based information systems. Quality of Service (QoS) is defined as a measure of how well the network and is an attempt to define the characteristics and nature of the service. In an Internet Protocol (IP), IP QoS refers to the performance of the -Package IP packets passing through one or more networks. QoS is designed to help end users become more productive by ensuring that end users get reliable performance of network-based applications. QoS refers to the ability of a network to provide better service at a specific network traffic through different technologies. Computer network performance can vary due to several problems, such as problems of bandwidth, latency and jitter, which can make the effect is large enough for many applications. Features Quality of Service (QoS) can make the bandwidth, latency and jitter are predictable and matched to the needs of applications that are used in the existing network. Keywords – Quality of Service, Internet Protocol, Bandwith, latency, jitter